The influence of the learning together learning model on Grade x students - Rina Wati; Gina Sonia Amelya; Aguang Setiawan; Sri Wahyudi (Institute of Computer Science (IOCS), 2023)
This study aims to determine the influence of the Learning Together (LT) learning model on the learning outcomes of grade X students at SMK N 2 Rambah. The research method carried out in this study is Quasi Experiment by looking for influences between X and Y. the population in this study is class X students of SMK Negeri 2 Rambah totaling 33 students with sampling techniques using saturated samples of all populations into samples. The method of data collection is carried out using tests. Test the validity of the test instrument using the product moment relationship technique The prerequisite test of analysis consists of a normality test and a homogeneity test. The results of the study provide that the Learning Together (LT) learning model has a very positive effect on the learning outcomes of students at SMK N 2 Rambah.